2019
DOI: 10.1519/ssc.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Demands of Youth Artistic Gymnastics: Applications to Strength and Conditioning

Abstract: The sport of artistic gymnastics involves a series of complex events that can expose young gymnasts to relatively high forces. The sport is recognized as attracting early specialization, in which young children are exposed to a high volume of sports-specific training. Leading world authorities advocate that young athletes should participate in strength and conditioning related activities in order to increase athlete robustness and reduce the relative risk of injury. The purpose of this commentary is to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 91 publications
(118 reference statements)
0
31
0
3
Order By: Relevance
“…These specific tests were selected from the full FMS due to their significant correlations with measures of physical performance in youth [23]. The tests also provided an assessment of the gymnasts’ bilateral and unilateral lower limb movements, both of which are integral to gymnastics performance [6]. Each gymnast performed three trials of both tests and were scored real-time using the 4-point scale from the FMS movement criteria (the rater had 2 years of experience using this screening tool) [24,25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These specific tests were selected from the full FMS due to their significant correlations with measures of physical performance in youth [23]. The tests also provided an assessment of the gymnasts’ bilateral and unilateral lower limb movements, both of which are integral to gymnastics performance [6]. Each gymnast performed three trials of both tests and were scored real-time using the 4-point scale from the FMS movement criteria (the rater had 2 years of experience using this screening tool) [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Since relative strength is a more important determinant of gymnastics performance than absolute strength [2], it is unsurprising that many coaches traditionally use body-weight training in the form of circuits and repetition of skills to physically prepare gymnasts [3]. However, while this training modality is often effective in developing highly sport-specific qualities, the addition of developmentally appropriate neuromuscular training could offer pre-pubertal gymnasts’ numerous benefits, that surpass body-weight and skills training alone [4,5,6]. Research suggests that neuromuscular training which integrates the development of fundamental movement skills with muscular strength and power could facilitate technical competency of sport-specific skills [7,8], assist in correcting aberrant movement patterns [9,10,11], and help promote long-term participation in competitive and recreational sport [8].…”
Section: Introductionmentioning
confidence: 99%
“…[50]. Further, three of the four artistic disciplines that female gymnasts compete in (vault, beam and floor exercise) are heavily reliant on explosive lower-limb rebounding and jumping activities, which all utilize various expressions of the stretch-shortening cycle (SSC) [36]. Consequently, rebounding and jumping performance of artistic gymnasts are commonly assessed to identify key determinants of the sport [8,29,31,50], determine physical profiles [46,53] and evaluate the efficacy of training interventions [7,11,28,37].…”
Section: Introductionmentioning
confidence: 99%
“…However, while this training is commonly used in gymnastics to develop sport-specific fitness, the addition of an age appropriate, supplementary, strength and power training program may offer positive outcomes that surpass the benefits obtained by skills training alone [26,28]. Previous studies suggested that supplementary strength and power training using basic movement skills, may enhance technical competency, correct movement patterns, and reduce injury risk [26,29] especially in adolescent female athletes, who show decreased strength and increased injury risk compared to males [30,31]. An important limitation of the existing training practice schedules in most youth sports is that training time per session (typically 1.5 h) may not be sufficient for learning new skills and improving muscular fitness.…”
Section: Introductionmentioning
confidence: 99%